Gideon's revolution : a novel - Carso, Brian F., Jr (Three Hills, an imprint of Cornell University Press, 2023)
"A historical novel based on the true story of a plot for American spies to capture Benedict Arnold in British-occupied New York following Arnold's treason at West Point"--